Study of interstitial oxygen mobility in RuSr2GdCu2O8 by internal friction - Gimenez, J. M. A. [UNESP]; Grandini, Carlos Roberto [UNESP]; Jurelo, A. R. (Elsevier B.V. Sa, 2009)
The discovery of the spatial uniform coexistence of superconductivity and ferromagnetism in ruthenocuprates, RuSr2GdCu2O8 (Ru-1212), has spurred an extraordinary development in the study of the competition between magnetism and superconductivity. However, several points of their preparation process and characterization that determine their superconductive behaviour are still obscure. The improvement of sample preparation conditions involves some thermal treatments in inert atmosphere. Anelastic spectroscopy measurements were made using an inverted torsion pendulum, operating with an oscillation frequency of 38 Hz, temperature in the 90 and 310 K range, heating rate of 1 K/min, and vacuum better than 10(-3) Pa. The results show anelastic relaxation peaks at 210 K related to the presence of interstitial oxygen atoms. The peaks decrease significantly with the oxygen loss caused by the heat treatments in vacuum, appearing again after the annealing of the sample in an oxygen atmosphere. These observed peaks are clearly related to the additional oxygen atoms, with activation energy 0.13 and 0.36 eV, and can be explained in terms by diffusional jumps of interstitial oxygen in the RuO2 planes. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Anelastic spectroscopy; Ru-1212; Torsion pendulum; Oxygen mobility